Preclinical study of the thymoanaleptic effect of furylated dihydropyridine-2-thiol derivatives of alpha-cyanothioacetamide in a haloperidol catalepsy test - V. S. Subbota; E. Yu. Bibik; S. G. Krivokolysko (Сибирский научный медицинский журнал, 2025)
Over the past decades, there has been a steady increase in the incidence of depressive disorders. Modern antidepressants predominantly are drugs with a high incidence of side effects and drug interactions. The aim of the study is to investigate the thymoanaleptic effect of new substances of the substituted furylated nitrogen-containing heterocyclic derivatives of alpha-cyanothioacetamide in the haloperidol-induced catalepsy test. Material and methods. The experiments were performed on 110 animals divided into 11 groups: a control group, two comparison groups (comparison drugs – amitriptyline and fluoxetine), eight experimental groups (respectively, eight experimental samples). In the haloperidolinduced catalepsy test, the effectiveness of furylated dihydropyridine-2-thiols with codes d02-20, CV-103, AZ-381, AZ-127, d02-26, CV-133, AZ-618, AZ-128, which have already shown thymoanaleptic properties in the tail suspension and forced swimming tests, as well as anxiolytic properties in the dark-light chamber test, was studied.Results and discussion. Fluoxetine was more effective in eliminating the cataleptogenic effect of the typical neuroleptic haloperidol than amitriptyline. The absolute leaders in terms of thymoanaleptic properties under this technique are AZ-127 and AZ-128 compounds (p < 0.01 relative to amitriptyline and fluoxetine at each time point). Sample d02-20 also showed high activity, exceeding the efficacy of amitriptyline (p < 0.01 relative to amitriptyline at each time point), (the overall effectiveness is 47.64 % and 67.51 % higher than fluoxetine, respectively). Conclusions. High antidepressant activity of alpha-cyanothioacetamide derivatives AZ-127, AZ-128, d02-20d02-26 was revealed.